Thermoresponsive drug controlled release from chitosan‐based hydrogel embedded with poly(N‐isopropylacrylamide) nanogels. Issue 17 (10th August 2018) - Shin, Bomina; Kim, Jongjun; Vales, Temmy Pegarro; Yang, Si Kyung; Kim, Jong‐Ki; Sohn, Honglae; Kim, Ho‐Joong
ABSTRACT: A facile synthetic strategy was developed for the preparation of thermoresponsive nanocomposite hydrogels comprising crosslinked chitosan (CS) networks and poly( N ‐isopropylacrylamide) [p(NIPAAm)] nanogels. First, thermoresponsive p(NIPAAm) nanogels were synthesized via emulsion polymerization. The p(NIPAAm) nanogels were introduced into methacrylamide CS (MC) solution and the free‐radical initiated crosslinking reaction of MC produced nanogel‐embedded hydrogels. The last step involves the loading of the antibacterial model drug levofloxacin (LFX) into the prepared nanocomposite hydrogels by allowing the preformed hydrogels to swell to equilibrium in the drug's aqueous solution. The integration of p(NIPAAm) nanogel into CS networks facilitates thermoresponsive release of LFX with an enhancement of the drug‐loading capacity within the hydrogel. Notably, thermoresponsive drug‐release was achieved without unwarranted modification of the hydrogel's dimension and shape, although an increase in temperature caused the collapse of the p(NIPAAm) nanogels. The thermoresponsive property of the investigated nanocomposite hydrogel is beneficial and may offer broad opportunities for drug temperature‐triggered release for clinical applications. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1907–1914 Abstract : A chitosan‐based hydrogel embedded with thermoresponsive p(NIPAAm) nanogels was designed, synthesized, and evaluated as the drug carrier. Remarkably, nanocomposite hydrogels demonstrated thermoresponsive release of levofloxacin with an enhancement of the drug‐loading capacity within the hydrogel. The controlled drug‐release profiles depend on the temperature‐aided collapse of p(NIPAAm) shells and the influence of diffusion on drug transport.